Biomechanical evaluation of the modified proximal femoral nail for the treatment of reverse obliquity intertrochanteric fractures - Qian Wang; Liang Sun; Lu Liu; Teng Ma; Zhong Li; Kun Zhang; Qiang Huang (Scientific Reports)
Abstract The best treatment method for reverse obliquity intertrochanteric fractures (ROIFs) is still under debate. Our team designed the modified proximal femoral nail (MPFN) specially for treating such fractures. The objective of this research was to introduce the MPFN device and compare the biomechanical properties with Proximal Femoral Nail Antirotation (PFNA) and InterTAN nail via finite element modelling. An AO/OTA 31-A3.1 ROIF model was established via Mimics software. Three implants were depicted and assembled on the ROIF models. The axial, bending, and torsion loads were simulated to test stress and displacement of three fixation models. Compared to the PFNA and InterTAN models, the MPFN model had more dispersed stress distribution under axial loads of 2,100 N. The MPFN showed lower von Mises stress on bones compared with that of PFNA and InterTAN in axial loads. In term of maximum displacement, the MPFN had a 12.6% reduction compared to the PFNA model in axial load case. In bending and torsion loads, the MPFN model also demonstrated better biomechanical properties than the PFNA and InterTAN models. The modified proximal femoral nail presented the best biomechanical performance, followed by the InterTAN nail, and the PFNA for fixing reverse obliquity intertrochanteric fractures. The MPFN has the potential to be a promising device for patients with ROIFs.